Efektivitas Liquid Suction Heat Exchanger (LSHX) pada Mesin Refrigerasi dengan R404A pada Berbagai Tingkat Subcooling - Andriyanto Setyawan (Retii, 2018)
Liquid-to-suction heat exchanger has been used for air conditioning and refrigeration machines over years. It is aimed to increase the cooling capacity and coefficient of performance. In this research, the influence of LSHX utilization on a refrigerating machine with refrigerant R404a has been tested. The test was focused on the heat exchanger effectiveness under various evaporating temperature. To vary the evaporating temperature, a valve has been installed on the inlet side of thermostatic expansion valve. By varying the openings of this valve, the pressure of suction line could be varied from 30 psi to 50 psi, results in the evaporating temperatures from -24°C to -10°C. With the LSHX, the liquid refrigerant temperature could be lowered by 4°C to 8°C. The reduction of the temperature improves the capacity and coefficient to performance up to 16%. Based on the experimental results, the effectiveness of the LSHX ranges from 0.18 to 0.25. The lower the evaporating temperature gives the higher the effectiveness of the LSHX. However, subcooling and superheating should be limited to a certain value in order to control the compressor within safe operating conditions.